Exposição à radiação ionizante da equipe de enfermagem de um Centro de Terapia Intensiva adulto de um hospital universitário - Barbosa, Livia Santana (2021)
INTRODUCTION: In Intensive Care Units, mobile X-ray equipment is responsible for emitting radiation that can be harmful to health. OBJECTIVES: to measure the dose of ionizing radiation that the workers of the nursing staff of the Adult ICU, at a large University Hospital, are exposed to during an image exam using a mobile X-ray machine, and verify the team's level of understanding in relation to IR and the use of radiological protection equipment. METHODOLOGY: This was a quantitative, descriptive and prospective study, carried out in the Adult ICU of a large University Hospital. The sample consisted of nursing assistants and technicians and nurses (N = 54 professionals), of these 46 individuals answered the questionnaire applied and 8 were excluded for being on vacation (04) and having a medical certificate (04). The data collection instrument was a structured questionnaire that allowed the characterization of the sample with socio-professional and socio-economic data, in addition to raising information on the use of radiological protection equipment and the level of knowledge on the subject. The second part of data collection was carried out through the fixation of individual dosimeters arranged in 15 beds selected by drawing lots and in the common areas of the sector. The IR dose was monitored using Optically Stimulated Dosimetry, using carbon-doped aluminum oxide dosimeters. RESULTS: 85.2% of the sample participated in the survey. Of these, 78.2% were female; 47.8% were nursing technicians; 65.2% were working in the sector for between 01 and 10 years; 97.8% did not use any type of radiological protection; only 26.1% knew the topic during their professional training; none had in-service RI education. All monitors recorded a dose less than 0.1 mili Sievert (mSv), which means a dose below the recording level, ie, below 0.2mSV. DISCUSSION: The nursing staff at the Adult ICU worked in the sector from 01 to 10 years, different from what was found in Rio Grande do Sul (average of 17.6 years). Most nursing workers do not wear PPE during the X-ray exam, a similar study showed an absence of RPV (Radiological Protection Clothing) in the ICU. 73.9% of nursing workers were exposed to IR on a daily and periodic basis. This same result was found in a Hospital in João Pessoa. Most respondents did not have access to the topic of IR during their professional training, especially the technical course. In the research carried out in Teresina, the discipline of radiology is not included in the curriculum of nursing courses. CTI Adult did not have an in-service education program. The dosimeters showed RI doses lower than 0.1 mSv which showed a dose below the recording level. In 2014, a similar result was also found in a large Indian hospital. FINAL CONSIDERATIONS: This result confirmed that the team develops its work activities in a safe environment, however, the risks caused by stochastic effects should not be disregarded.